Checked corecursive streams: Expressivity and completeness - Ancona, Davide; Barbieri, Pietro; Zucca, Elena (Theoretical computer science, 2023)
Checked corecursive streams are a novel approach to stream definitions relying on a semantics of function application detecting cyclic calls, and a well-definedness check ensuring that access to an arbitrary index will always return a result. We extend the technique beyond the simple stream operators considered in previous work, notably by adding an interleaving combinator which has a non-trivial recursion scheme. We show that this actually enhances expressive power, since the interleaving operator cannot be expressed by the others, and that it is still possible to perform a sound and complete well-definedness check, through a symbolic computation which mimics access to an arbitrary index. •Formal investigation of the expressive power of the calculus.•Proof that the interleaving operator cannot be expressed by other operators.•Enhanced well-formedness runtime check sound and complete with respect to termination of access.